Artemisia anomala Herba Alleviates 2,4-Dinitrochlorobenzene-Induced Atopic Dermatitis-Like Skin Lesions in Mice and the Production of Pro-Inflammatory Mediators in Tumor Necrosis Factor Alpha-/Interferon Gamma-Induced HaCaT Cells - Ju-Hye Yang; Kwang-Youn Kim; Young-Woo Kim; Kwang-Il Park (Molecules, 2021)
Artemisia anomala S. Moore is a perennial herbaceous plant classified as Asteraceae of the genus Artemisia. Many species of Artemisia have been used as medicinal materials. Artemisia anomala S. Moore has been widely used in China to treat inflammatory diseases. However, the mechanism of its action on the keratinocyte inflammatory response is poorly understood. Here, we investigated the anti-inflammatory reaction of Artemisia anomala S. Moore ethanol extract (EAA) using human keratinocyte (HaCaT) cells, which involved investigating the nuclear factor kappa B (NF-κB), signal transducer, and activator of transcription-1 (STAT-1), as well as mitogen-activated protein kinase (MAPK) signaling pathways and atopic dermatitis-like skin lesions in mice. We elucidated the anti-inflammatory effects of EAA on tumor necrosis factor-α/interferon-γ (TNF-α/IFN-γ)-treated human keratinocyte cells and 2,4-dinitrochlorobenzene (DNCB)-induced atopic dermatitis (AD)-like mice. The levels of chemokines and cytokines (IL-8, IL-6, TARC, and RANTES) were determined by an enzyme-linked immunosorbent assay. The NF-κB, STAT-1, and MAPK signaling pathways in HaCaT cells were analyzed by western blotting. Thickening of the mice dorsal and ear skin was measured and inflammatory cell infiltration was observed by hematoxylin and eosin staining. Results showed that EAA suppressed IL-8, IL-6, TARC, and RANTES production. EAA inhibited nuclear translocation of NFκB and STAT-1, as well as reduced the levels of phosphorylated ERK MAPKs. EAA improved AD-like skin lesions in DNCB-treated mice. These findings suggest that EAA possesses stronger anti-inflammatory properties and can be useful as a functional food or candidate agent for AD.